Wettability of Polar and Apolar Liquids on Metal Surfaces - Mohanad Khairi; Zoltán Erdélyi; Peter Baumli (Metals)
The wettability of metal surfaces by different oils and water is a multifaceted phenomenon with significant implications for industrial processes, including lubrication, corrosion protection, and fluid transport; an understanding of the process is essential for optimizing the performance and durability of metallic components. The intermolecular interactions between oil molecules and the metal surface primarily influence the wetting of a metal surface by different types of oil. This paper introduces the concept of oil wetting on metal surfaces, exploring the factors influencing wetting behavior, the characterization techniques employed to assess wetting properties, and the implications for different industrial processes. This work aims to ascertain the contact angle of oil on various metal surfaces and subsequently establish a relationship between this contact angle and the attributes of the substrate. This is achieved through using the sessile drop technique. The results indicate that the wettability of petroleum was better than the hydraulic oil we used on all types of substrates (for example, on Ag surface, Θ-petroleum = 11°, but Θ-hydraulic oil = 20°). Also, we observed that the cosine of the oil/metal contact angle increases with the increase in the atomic radius of the pure metal substrate, and Becker’s broken bond model proved this linear relation. We then contrast this behavior with the wetting characteristics of water and glycerin on the same metals using the same conditions.